Social contexts of trauma and healing - Ajduković, Dean (Array, 2004)
The social contexts in which the mass trauma of thousands of people occur and in which their recovery should progress have qualities that distinguish them in important ways from individualized trauma in which a person is a victim of a violent attack, rape or a traffic accident. Organized violence, such as wars, oppression by dictatorships and massive terrorist attacks are extreme cases in which hundreds and thousands of people are exposed to trauma in a short period of time. As such, it has multiple consequences that extend beyond the affected individuals and the symptoms they suffer. Although the symptoms may be similar, the social contexts in which individual victimization and exposure to organized violence happen, are very different. Likewise, the social milieu in which the survivor of individual trauma and survivors of mass trauma are embedded is different, having important consequences for recovery. Understanding the social context of the trauma helps create the right social interventions for healing at social and personal levels.